Ծաղկատման ազդեցությունը ծխախոտի Սամսուն 36 սորտի կենսարդյունավետության վրա - Ռ. Կ. Սիմոնյան (ՀՀ ԳԱԱ հրատ.)
Հոդվածում քննարկվում է ծաղկատման ազդեցությունը ծխախոտի բուրավետ խմբի Սամսուն 36 սորտի բույսերի կենսարդյունավետության վրա:В статье обсуждается влияние дефлорации на продуктивность растений табака сорта Самсун 36, принадлежащего к ароматической группе табака. Показано, что дефлорация вносит существенные изменения в динамику интенсивности фотосинтеза в процессе вегетации. The article discusses defloration’s influence on the plants bioproductivity of tobacco fragrant group’s sort Samsun 36. It is shown, that defloration cause essential alterations in vegetation course on dinamic of photosynthesis intensivity, promote the growth of vegetative organs and increase in dry weight and materiality of leafs.
Keywords: Agriculture; Plants; Biology; Biometrics